An Overview on The Key Issues of Microgrid - Mujahid Irfan, Md.; Verma, Nidhi; Ram Deshmukh, Dr.; Rajamallaiah, A. (International Journal of Engineering and Technology, 2018)
The demand for high quality electricity and growing electricity consumption has been caused by increasing charge of day by day life causes and the rising number of delicate or critical loads. Because of the quick increase in worldwide energy consumption and the diminishing of petroleum derivatives, the customer demand for new generation limits and effective energy production, delivery and use continues rising. Microgrids are becoming increasingly alluring to customers and in that capacity later on, an extraordinary number of them will be installed at purchaser's locales. In this circumstance, regular distribution networks that acknowledge distributed generation associations may confront genuine trouble when its control and protection functions turn out to be more muddled. This incurs a weight to the system task and some specialized constraints will show up when an incredible number of distributed generations are installed. One method for overcoming such issues, a micro grid system is shaped to give solid electricity and warmth delivering administrations by connecting distributed generations and loads together within a little area.The micro grid idea can possibly take care of significant issues arising from extensive entrance of distributed generation in distribution systems. A legitimate control technique ought to be actualized for a fruitful task of a micro grid . Diverse load models can be reproduced and dissected using MATLAB and PSCAD programming. In this paper, the work done in the field of Micro Grid has been reviewed.Â Â